Breast Fibromatosis: Radiologic–Pathologic Correlation. Issue 5 (9th August 2021) - Winkler, Nicole; Peterson, Michael; Factor, Rachel
Abstract: Fibromatosis of the breast is a rare, benign locally infiltrative tumor without metastatic potential. Patients typically present with a painless, palpable, firm breast mass, which may be mobile or fixed to the pectoralis muscle. While some cases are related to familial mutations in the adenomatous polyposis coli ( APC ) gene, the majority are sporadic due to somatic mutations or prior injury to the breast tissue. On mammography, fibromatosis is typically seen as an irregular, dense, spiculated mass. US demonstrates a hypoechoic, irregular mass with indistinct margins. Fibromatosis is indistinguishable from breast cancer on imaging, and core biopsy is required for definitive diagnosis. Wide local excision is the historical standard for treatment; however, recurrence rates are high, and other emerging therapies are being explored. This article reviews the clinical features, imaging and histopathologic findings, along with brief overview of management.